The influence of Brazilian plant extracts on Streptococcus mutans biofilm - Michele BARNABÉ; Cíntia Helena Coury SARACENI; Maristela DUTRA-CORREA; Ivana Barbosa SUFFREDINI (University of São Paulo, 2014)
Nineteen plant extracts obtained from plants from the Brazilian Amazon showed activity against planktonic Streptococcus mutans, an important bacterium involved in the first steps of biofilm formation and the subsequent initiation of several oral diseases. Objective: Our goal was to verify whether plant extracts that showed activity against planktonic S. mutans could prevent the organization of or even disrupt a single-species biofilm made by the same bacteria. Material and Methods: Plant extracts were tested on a single-bacteria biofilm prepared using the Zürich method. Each plant extract was tested at a concentration 5 times higher than its minimum inhibitory concentration (MIC). Discs of hydroxyapatite were submersed overnight in brain-heart infusion broth enriched with saccharose 5%, which provided sufficient time for biofilm formation. The discs were then submersed in extract solutions for one minute, three times per day, for two subsequent days. The discs were then washed with saline three times, at ten seconds each, after each treatment. Supports were allowed to remain in the enriched medium for one additional night. At the end of the process, the bacteria were removed from the discs by vortexing and were counted. Results: Only two of 19 plant extracts showed activity in the present assay: EB1779, obtained from Dioscorea altissima, and EB1673, obtained from Annona hypoglauca. Although the antibacterial activity of the plant extracts was first observed against planktonic S. mutans, influence over biofilm formation was not necessarily observed in the biofilm model. The present results motivate us to find new natural products to be used in dentistry.